2004
DOI: 10.1038/sj.gt.3302178
|View full text |Cite
|
Sign up to set email alerts
|

Induction of immune tolerance to a transplantation carbohydrate antigen by gene therapy with autologous lymphocytes transduced with adenovirus containing the corresponding glycosyltransferase gene

Abstract: Induction of tolerance to transplantation carbohydrate antigens is of clinical significance in recipients of ABOincompatible allografts, or of xenografts. The experimental animal model used for studying such tolerance was that of a1,3galactosyltransferase (a1,3GT) knockout (KO) mice, which lacks the a-gal epitope (Gala1-3Galb1-4GlcNAc-R) and which can produce the anti-Gal antibody against it. In contrast, wild-type (WT) mice synthesize the a-gal epitope and are immunotolerant to it. KO lymphocytes transduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The application of gene therapy as a means to achieve tolerance was first reported in aGT À/À knockout mice transplanted with BM, transduced with a murine retrovirus encoding the aGT enzyme. 8 We reported that permanent tolerance to gal + hearts can be achieved in this animal model using lentiviral vectors, 9 and Ogawa et al 10 reported similar results using transfer of adenovirus-transduced, autologous splenic lymphocytes. More recently, we have shown that aGT-encoding lentivectors can achieve sufficient chimerism in aGT À/À mice to result in permanent tolerance to gal + hearts following sublethal irradiation.…”
Section: Introductionsupporting
confidence: 49%
“…The application of gene therapy as a means to achieve tolerance was first reported in aGT À/À knockout mice transplanted with BM, transduced with a murine retrovirus encoding the aGT enzyme. 8 We reported that permanent tolerance to gal + hearts can be achieved in this animal model using lentiviral vectors, 9 and Ogawa et al 10 reported similar results using transfer of adenovirus-transduced, autologous splenic lymphocytes. More recently, we have shown that aGT-encoding lentivectors can achieve sufficient chimerism in aGT À/À mice to result in permanent tolerance to gal + hearts following sublethal irradiation.…”
Section: Introductionsupporting
confidence: 49%
“…by guest www.bloodjournal.org From Several laboratories are studying the application of gene therapy to achieve tolerance to the ␣Gal carbohydrate. 17,18,37 Ogawa et al 37,38 and Mohiuddin et al 39 have reported the induction of tolerance in GalT Ϫ/Ϫ mice using autologous lymphocytes transduced with an adenovirus vector expressing GalT. Since the transduced splenic lymphocytes demonstrate limited survival, these reports suggest that long-term, high-level chimerism in PBCs is not necessary for stable tolerance induction.…”
Section: Discussionmentioning
confidence: 89%
“…The assumption that AdaGT can induces expression of a-gal epitopes on lymphoid cells is supported by our previous studies, which demonstrated the effective expression of a-gal epitopes on normal lymphocytes obtained from KO mice. 66 We further demonstrated expression of a-gal epitopes on human cells with the HeLa carcinoma cell line transduced with AdaGT. 55 Taken together with the present study, these observations suggest that expression of a-gal epitopes may also be achieved on malignant human lymphocytes processed as autologous tumor vaccines, by similar transduction with AdaGT.…”
Section: Discussionmentioning
confidence: 99%